2010
DOI: 10.1071/rd09223
|View full text |Cite
|
Sign up to set email alerts
|

Practical applications of new research information in the practice of bovine embryo transfer

Abstract: For more than 40 years, practitioners have sought to improve all aspects of commercial bovine embryo transfer. The development of new technologies for this industry has been substantial, with recent focus on cryopreservation techniques and the in vitro production of embryos fertilised with sexed spermatozoa. When these and other new technologies are developed, the following questions remain: (1) is said technology regulated or does it require licensing; and (2) is it applicable and, if so, is it financially fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…However, the quality of the embryos varies and may be affected by oocyte competence or during embryo development in the oviduct (Killian 2004;Looney and Pryor 2010). Oocyte competence seems to be related to the abundance of specific mRNA that is transcribed and accumulated during oocyte growth and the final phases of folliculogenesis.…”
Section: Role Of Lhr In Follicular Deviation In Cattlementioning
confidence: 99%
“…However, the quality of the embryos varies and may be affected by oocyte competence or during embryo development in the oviduct (Killian 2004;Looney and Pryor 2010). Oocyte competence seems to be related to the abundance of specific mRNA that is transcribed and accumulated during oocyte growth and the final phases of folliculogenesis.…”
Section: Role Of Lhr In Follicular Deviation In Cattlementioning
confidence: 99%
“…Similarly, in cattle, despite constant refinement of ovulation induction protocols, mainly driven by more efficient management demands, embryo yield per superovulated donor has not changed significantly (Bó et al, 2008). The yield and the quality of embryos produced following ovulation induction of cattle are highly variable and may be affected either through effects on the oocyte during follicular growth (Sirard et al, 2006) or directly during embryo development in the oviduct and/or uterus (Killian, 2004;Looney and Pryor, 2010). It is clear that oocytes and embryos in superovulated animals develop under abnormal endocrine conditions, which differ substantially from those in unstimulated (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the yield of embryos produced through the induction of superovulation can be highly variable and negatively influenced by factors such as the effects on the oocyte during follicular growth or directly during embryo development in the oviduct and/or uterus (105,106). The mechanism by which oocytes and embryos develop under hormonal superstimulation has an effect on abnormal endocrine conditions compared to those developed in unstimulated animals, ultimately leading to low developmental potential (107).…”
Section: The Consequences Of Superovulation For Oocytes and Embryosmentioning
confidence: 99%